Recognizing catastrophic incident warning signs in the process industries - American Institute of Chemical Engineers. Center for Chemical Process Safety (Hoboken, N.J. : John Wiley & Sons, 2012)
'This book provides guidance on characterizing, recognizing, and responding to warning signs to help avoid process incidents and injuries before they occur. The guidance can be used by both process safety management (PSM) professionals in evaluating their processes and PSM systems as well as for operators who are often the frontline defense against process incidents. Warning signs may consist of process deviations or upsets, instrumentation warnings or alarms, past operating history and incidents, observable problems such as corrosion or unusual odors, audit results indicating procedures are not being followed, or a number of other indicators. Filled with photos and practical tips, this book will turn anyone in a process plant into a hazard lookout and will help prevent potential incidents before they turn into catastrophic events'--
Includes index.
Keywords: Chemical engineering -- Safety measures; Chemicals -- Accidents -- Prevention; Warnings